Role of glycosylation on the ensemble of conformations in the MUC1 immunodominant epitope. (14th November 2019) - Singh, Jaideep; Her, Cheenou; Supekar, Nitin; Boons, Geert‐Jan; Krishnan, Viswanathan V.; Brooks, Cory L.
Abstract : MUC1 is a membrane glycoprotein, which in adenocarninomas is overexpressed and exhibits truncated O‐glycosylation. Overexpression and altered glycosylation make MUC1 into a candidate for immunotherapy. Monoclonal antibodies directed against MUC1 frequently bind an immunodominant epitope that contains a single site for O‐glycosylation. Glycosylation with tumor carbohydrate antigens such as the Tn‐antigen (GalNAc‐O‐Ser/Thr) results in antibodies binding with higher affinity. One proposed model to explain the enhanced affinity of antibodies for the glycosylated antigen is that the addition of a carbohydrate alters the conformational properties, favoring a binding‐competent state. The conformational effects associated with Tn glycosylation of the MUC1 antigen was investigated using solution‐state NMR and molecular dynamics. NMR experiments revealed distinct substructures of the glycosylated MUC1 peptides compared with the unglycosylated peptide. Molecular dynamics simulations of the MUC1 glycopeptide and peptide revealed distinguishing differences in their conformational preferences. Furthermore, the glycopeptide displayed a smaller conformational sampling compared with the peptide, suggesting that the glycopeptide sampled a narrower conformational space and is less dynamic. A comparison of the computed ensemble of conformations assuming random distribution, NMR models, and molecular dynamics simulations indicated that the MUC1 glycopeptide and aglycosylated peptide sampled structurally distinctly ensembles and that these ensembles were different from that of the random coil. Together, these data support the hypothesis that that conformational pre‐selection could be an essential feature of these peptides that dictates the binding affinities to MUC1 specific antibodies. Abstract : Antibodies directed against the tumor antigen MUC1 frequently bind an epitope that contains an O‐glycosylation site. Glycosylation with the Tn‐antigen can alter antibody affinity for MUC1. NMR experiments revealed distinct substructures of a Tn‐glycosylated MUC1 peptide compared to the aglycosylated form. Comparison of computed ensembles, NMR models and MD simulations indicated that theglycosylated and aglycosylated peptides sampled distinct conformations. These data support the hypothesis that conformational pre‐selection is essential feature that dictates the affinity of antibodies to MUC1.